1994
DOI: 10.1002/hep.1840200629
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by recombinant human interleukin-6 of the glucagon-dependent induction of phosphoenolpyruvate carboxykinase and of the insulin-dependent induction of glucokinase gene expression in cultured rat hepatocytes: Regulation of gene transcription and messenger RNA degradation

Abstract: The influence of recombinant human interleukin-6, the major mediator of the inflammatory response in liver, on the glucagon- and insulin-dependent induction of the phosphoenolpyruvate carboxykinase and glucokinase gene, respectively, was monitored on the level of gene transcription, mRNA abundance and enzyme activity in cultured rat hepatocytes. As control markers of the interleukin-6-induced acute-phase response the mRNA levels of the acute phase proteins alpha 2-macroglobulin and beta-fibrinogen were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
2
29
0
2
Order By: Relevance
“…This may suggest that IL-6 can actually improve hepatic insulin resistance in patients with Type 2 diabetes. In contrast, IL-6 also inhibits insulin activation of glucokinase [85] while it has been shown to induce hepatic triglyceride secretion in rats [86]. As discussed, chronic treatment with IL-6 induces hepatic insulin resistance in rats, due to marked reductions in insulin receptor autophosphorylation and IRS-1 tyrosine phosphorylation [64].…”
Section: Interaction Between Il-6 and Glucose Transport In Vivomentioning
confidence: 95%
“…This may suggest that IL-6 can actually improve hepatic insulin resistance in patients with Type 2 diabetes. In contrast, IL-6 also inhibits insulin activation of glucokinase [85] while it has been shown to induce hepatic triglyceride secretion in rats [86]. As discussed, chronic treatment with IL-6 induces hepatic insulin resistance in rats, due to marked reductions in insulin receptor autophosphorylation and IRS-1 tyrosine phosphorylation [64].…”
Section: Interaction Between Il-6 and Glucose Transport In Vivomentioning
confidence: 95%
“…PGE 2 has previously been shown to mimic the action of IL-6 as an inhibitor of the glucagon-elicited induction of the key gluconeogenetic enzyme phosphoenolpyruvate carboxykinase via the G i -linked EP3-R. 45 This inhibition of the glucagoninduced transcription of the phosphoenolpyruvate carboxykinase gene may represent the hepatocyte' s strategy to economize its resources for the acute phase response. 46 PGE 2 has also been shown to increase the ␣ 2 -MG formation in unstimulated hepatocytes 21 via an as yet unidentified receptor. These actions of PGE 2 indicate that it may be considered an enhancer of the acute phase reaction.…”
Section: G S -Coupled Prostanoid Receptors In Hepatocytesmentioning
confidence: 99%
“…IL-6 has also been implicated in the regulation of these genes. Studies using cultured rat hepatocytes showed that incubation with IL-6 attenuated glucagon-induced Pepck (also known as Pck1) expression [4] or inhibited dexamethasone/cAMP-induced Pepck and G6pase (also known as G6pc) expression [5]. Intraperitoneal application of IL-6 inhibited the increase in Pepck mRNA during the initial phase of fasting in rats [6].…”
Section: Introductionmentioning
confidence: 99%